2007
DOI: 10.1002/mds.21580
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal deep brain stimulation in patients with cranial–cervical dystonia (Meige syndrome)

Abstract: Idiopathic cranial-cervical dystonia (ICCD) is an adult-onset dystonia syndrome affecting orbicularis oculi, facial, oromandibular, and cervical musculature. ICCD is frequently difficult to treat medically. Deep brain stimulation (DBS) of the globus pallidus internus (GPi) is a highly effective treatment for idiopathic generalized dystonia, however less is known about the effect of GPi DBS on ICCD. In this article, we present the results from a pilot study assessing the effect of GPi DBS in a series of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
1
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(122 citation statements)
references
References 26 publications
7
111
1
3
Order By: Relevance
“…Since Vercueil and coworkers 3 first reported their results of bilateral GPi DBS in a patient with Meige syndrome, several studies have shown that segmental dystonia responds to GPi DBS. 2,3,6,9,11,13,[18][19][20][21][22][23][24][25][29][30][31] The reports on Meige syndrome and its response to DBS are primarily single cases, aside from the excellent report by Ostrem and colleagues 25 ( Table 3). The follow-up time frame has been somewhat limited in most reports, except the cases of Loher et al 21 at 7 years, Hebb et al 11 at 5 years, and Capelle and associates 6 at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Vercueil and coworkers 3 first reported their results of bilateral GPi DBS in a patient with Meige syndrome, several studies have shown that segmental dystonia responds to GPi DBS. 2,3,6,9,11,13,[18][19][20][21][22][23][24][25][29][30][31] The reports on Meige syndrome and its response to DBS are primarily single cases, aside from the excellent report by Ostrem and colleagues 25 ( Table 3). The follow-up time frame has been somewhat limited in most reports, except the cases of Loher et al 21 at 7 years, Hebb et al 11 at 5 years, and Capelle and associates 6 at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, bilateral stimulation is generally considered necessary for optimal treatment of disorders manifesting with midline symptoms, 9,25 and that unilateral stimulation may fail to alleviate the axial symptoms in patients with Meige syndrome. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been suggested that lead migration and lead fracture is more common in dystonia than in parkinsonian patients (Yianni et al, 2003). Stimulation-related adverse effects specific for GPi DBS in dystonia include the development of reversible bradykinesia and parkinsonian gait problems in previously nondystonic body regions (Berman et al, 2009;Ostrem et al, 2007;Zauber et al, 2009). …”
Section: Complicationsmentioning
confidence: 99%